A comprehensive review on performance and machinability of plant fiber polymer composites. Issue 1 (12th November 2021) - Mohit, Hemath; Mavinkere Rangappa, Sanjay; Siengchin, Suchart; Gorbatyuk, Sergey; Manimaran, P.; Alka Kumari, C.; Khan, Anish; Doddamani, Mrityunjay
Abstract: In recent years, the revolutionary utilization of plant fibers in polymer laminates significantly influenced environmental effects. Presently, there is progression attention in advancing bio‐based materials by acquiring plant fibers from lignocellulosic components for different applications like non‐structural, structural laminates, automobile components, ballistics, flooring, household utensils, and aerospace parts. These bio‐based, eco‐friendly components have been recognized as next‐generation contestants for higher‐efficacy, sustainable, cheap, environmentally friendly, and lightweight composites. Different kinds of synthetic and natural biopolymers and bio‐based nanoparticles have been applied to produce sustainable materials. Bio‐based polymer composites manifest unique characteristics of both eco‐reinforcement and sustainable resin. This review comprehensively communicates the general characteristics and principles of nanoparticles, polymers, and their respective composites. In addition to the machining characteristics, challenges and future perspectives of the polymer composites have also been reviewed.